Changes in spatial structures of plant communities lead to functional homogenization in an urban forest park. Issue 2 (1st February 2019) - Bergeron, Alexandre; Lavoie, Claude; Domon, Gérald; Pellerin, Stéphanie
Abstract: Aims: We investigated whether biotic homogenization of plant communities occurs over three decades in a small urban protected forest, and what the possible drivers are underlying the observed changes. Location: A 96 ha temperate forest, Montréal, Canada. Methods: We surveyed vegetation and explanatory variables (ecological conditions, disturbances, spatial structure) in 62 plant communities in 1980 and 2011. We collected plant attributes to identify functional groups (FGs). We evaluated changes in beta diversity using tests for homogeneity of multivariate dispersions. We used space–time interaction models to assess changes in FGs spatial structures. We used multivariate analyses to identify relationship between spatial patterns and explanatory variables, and variation partitioning analyses to identify the drivers involved in beta diversity changes. Results: Beta diversity declined only in the herb–shrub communities. About 35% of their FGs had significantly changed their spatial distribution over time. Those that contracted their distribution were mainly composed of plants with wind‐dispersed seeds or with low to intermediate vegetative propagation capabilities, while those that expanded were plants with fleshy fruits or extensive vegetative propagation capabilities. In 1980, communities were structured into small isolated clumps, while in 2011, clumps expanded and coalesced near disturbed areas. In 1980, the spatial assembly processes relied essentially on endogenous factors while in 2011 exogenous factors, such as disturbances, became more influential. Multivariate analyses suggested that edge effect, past agricultural disturbances, and beaver activities facilitated the decrease of beta diversity (homogenization process). Conclusions: The homogenization of herb–shrub communities likely resulted from changes in their clumped spatial structure. FGs with the most adapted attributes to disperse under urban forest conditions were those that expanded spatially. Structural changes seem to have begun with an unpredictable stage governed by dispersal limitation processes, followed by a predictable stage mostly driven by land‐use legacy and disturbances. Abstract : We documented changes over three decades in the plant functional communities of an urban protected forest. Beta diversity declined in the herb–shrub communities. Functional communities were originally structured into small isolated clumps that eventually expanded and coalesced. Structural changes began with an unpredictable stage governed by dispersal limitation processes, followed by a predictable stage mostly driven by land‐use legacy and disturbances.